English Language Writing Proficiency At The PMR Level: A Needs Analysis Study In A Rural Secondary School - PPIP, Pusat Pengajian Ilmu Pendidikan (2003)
The main contention of the findings of this study is poor writing skill causes poor performance in examinations Respondents committed basic errors mainly in grammar, sentence structure and vocabulary Elements of inappropriate classroom instructions were also detected which resulted in a mismatch between syllabus content and what was taught in class Obviously, certain writing needs of the students are not fulfilled accordingly. ThIS study. hav 109 identified the writing problems faced by the respondents, suggested some corrective measures and recommendations